2019
DOI: 10.25100/eg.v0i17.7918
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la evolución litoral y respuesta de las comunidades afro-descendientes asentadas en la zona costera: caso de estudio La Barra, Buenaventura, Pacífico Colombiano

Abstract: En el poblado de La Barra, Buenaventura (Colombia), desde el año 2013 inició un proceso de avulsión hacia el mar del estero Arrastradero, asociado a este evento se pudo medir un acelerado proceso de erosión costera que afectó el poblado en general. Con el fin de comprobar la hipótesis de que la dinámica litoral determina no solo la morfología de la costa sino también la dinámica poblacional, se evaluó la vulnerabilidad por erosión costera de la población, la evolución histórica y reciente de la línea de costa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This study used the COVI to estimate spatial vulnerability to coastal erosion through an analysis of coastal watersheds. The vulnerability in the Buenaventura area has been characterized by previous studies [13,[20][21][22]31,32]. However, an evaluation of its vulnerability to multiple risks and physical, environmental, and socioeconomic parameters, such as the COVI, has received minimal attention in studies on the coastal zone of Buenaventura.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study used the COVI to estimate spatial vulnerability to coastal erosion through an analysis of coastal watersheds. The vulnerability in the Buenaventura area has been characterized by previous studies [13,[20][21][22]31,32]. However, an evaluation of its vulnerability to multiple risks and physical, environmental, and socioeconomic parameters, such as the COVI, has received minimal attention in studies on the coastal zone of Buenaventura.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the CVI was used to assess vulnerability along the Atlantic coast by the United States Geological Survey (USGS) in the study of Thieler and Hammar-Klose [18]. In the analysis of coastline change, some studies focused on analyzing the geomorphological and physical factors of the CVI but also included socioeconomic variables to develop resilience to the threats of climate change [19][20][21][22][23][24]. The state of vulnerability can be determined based on a group of conditions and processes resulting from physical, environmental, and socioeconomic factors that increase the susceptibility of people living in coastal areas to natural hazards, including their ability to adapt and respond to disasters [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also includes the generation of information through the use of unmanned aerial vehicles (UAVs) to obtain high-resolution images and videos of the beach conditions (Parise et al, 2009). These tools are used in conjunction with global positioning systems (DGPS and GPS) to obtain the precise position of the beach line, which can subsequently be compared with historical cartographic data (Dillenburg et al, 2004;Esteves et al, 2006;Fernandez et al, 2011;Coca-Domínguez and Ricaurte-Villota, 2019;Martínez et al, 2022). They also include the use of Lidar to obtain high-resolution data of the topography of the area and field surveys to know the perception of the population and data related to impacts on infrastructures (Cueto et al, 2022;Simões FIGURE 14 Methods, tools, and data sources identified as relevant in the 62 case studies.…”
Section: Cluster 2: Fieldworkmentioning
confidence: 99%